Determinants of Adult Children Participation in Cocoa Production in Ondo-East Local Government Area of Ondo State, Nigeria - Ibidapo I.; Akintade T. F.; Ogunsipe M. H.; Amao O. (International Journal of Scientific Research in Science and Technology, 2024)
The study examined factors influencing adult children participation in cocoa production in Ondo-East Local Government Area of Ondo State, Nigeria. Multistage sampling procedure was used to select one hundred and twenty-eight (128) adult children for the study. Information was gathered on the socio-economic characteristics of adult children and their activities using a structured questionnaire. Data collected were analysed using descriptive statistics (mean, frequency counts, standard deviation) and the logit regression was used to analyse drivers of adult children participation in cocoa production in the study area. Results revealed the mean age of adult children was 35.62±3.87 years, 55.6% were male and 54.68% were married with mean household size of 6.0±3.0 members and average of 12.02 years of completed education. The activities engaged in by adult children included; weeding, scooping, fetching of water and breaking of cocoa pods, among others. The results of the logistic regression analysis revealed that, age, gender, household size, education, annual farm income, cultivated farm size and distance to farm were the significant variables influencing adult children participation in cocoa production at 5% level of significance. Adult children were found to be involved virtually in all aspects or activities in cocoa production. Education of adult children should be encouraged, more land should be provided to adult children to enhance cocoa production. Finally, access road should be rehabilitated and provided for increased productivity on the farm.
Keywords: Child Labour; Cocoa Production; Fetching Water; Participation